The road to 9/11 : wealth, empire, and the future of America - Scott, Peter Dale. (Berkeley : University of California Press, 2007)
This is an ambitious, meticulous examination of how U.S. foreign policy since the 1960s has led to partial or total cover-ups of past domestic criminal acts, including, perhaps, the catastrophe of 9/11. Peter Dale Scott, whose previous books have investigated CIA involvement in southeast Asia, the drug wars, and the Kennedy assassination, here probes how the policies of presidents since Nixon have augmented the tangled bases for the 2001 terrorist attack. Scott shows how America's expansion into the world since World War II has led to momentous secret decision making at high levels. He demonstrates how these decisions by small cliques are responsive to the agendas of private wealth at the expense of the public, of the democratic state, and of civil society. He shows how, in implementing these agendas, U.S. intelligence agencies have become involved with terrorist groups they once backed and helped create, including al Qaeda.
Nixon, Kissinger, and the decline of the public state -- The pivotal presidency : Ford, Rumsfeld, and Cheney -- Brzezinski, oil, and Afghanistan -- Carter's surrender to the Rockefellers on Iran -- Casey, the republican countersurprise, and the Bank of Credit and Commerce International, 1980 -- Afghanistan and the origins of al Qaeda -- The Al-Kifah Center, al Qaeda, and the U.S. Government, 1988-98 -- The Pre-9/11 cover-up of Ali Mohamed and al Qaeda -- Al Qaeda, the U.S. establishment, and oil -- Parallel structures and plans for continuity of government -- The 9/11 Commission report and Vice President Cheney -- The 9/11 Commission report's and Cheney's deceptions about 9/11 -- Cheney, the Federal Emergency Management Agency, and continuity of government.
Includes bibliographical references (pages 391-403) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Umschulungswerkstätten für Siedler und Auswanderer; Transparency (Ethics) in government -- United States; Privacy, Right of -- United States; War on Terrorism, 2001-2009 -- Political aspects; September 11 Terrorist Attacks, 2001 -- Political aspects; United States -- Politics and government -- 1945-1989.; United States -- Politics and government -- 1989-; Democracy -- United States; Elite (Social sciences) -- United States; National security -- United States; Political corruption -- United States -- History -- 20th century; Operation Enduring Freedom, 2001-2014 -- Political aspects; Transparence (Sciences sociales) -- États-Unis.; Droit à la vie privée -- États-Unis.; Opération Liberté immuable, 2001-2014 -- Aspect politique; Attentats du 11 septembre 2001, États-Unis -- Aspect politique; Démocratie -- États-Unis.; Élite (Sciences sociales) -- États-Unis.; Sécurité nationale -- États-Unis.; Corruption (Politique) -- États-Unis -- Histoire -- 20e siècle.; États-Unis -- Politique et gouvernement -- 1945-1989.; États-Unis -- Politique et gouvernement -- 1989-; Guerre contre le terrorisme, 2001-2009 -- Aspect politique; HISTORY -- United States -- 21st Century; HISTORY -- Middle East -- General; Democracy; Elite (Social sciences); National security; Political corruption; Politics and government; Privacy, Right of; Transparency in government; United States; Bekämpfung; Bürgerrecht; Elfter September; Geheimdienst; Politische Elite; Sicherheitspolitik; Terrorismus; USA; Buitenlandse politiek; 11 September 2001.; Verenigde Staten; Since 1900; History